2018
DOI: 10.1002/2211-5463.12454
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of IKKepsilon forms direct interactions with cytoskeletal proteins, tubulin and α‐actinin, linking innate immunity to the cytoskeleton

Abstract: Suppressor of IKK epsilon ( SIKE ) is associated with the type I interferon response of the innate immune system through TANK ‐binding kinase 1 ( TBK 1). Originally characterized as an endogenous inhibitor of TBK 1 when overexpressed in viral infection and pathological cardiac hypertrophic models, a mechanistic study revealed that SIKE acts as a high‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Similarly, FSIP1 regulates growth of triple-negative breast cancer cells and also resistance to docetaxel, a drug in the same class as paclitaxel (Liu, Sun, et al 2018). SIKE1 (Sonnenschein et al 2018) and CPT1A (Li, Zhao, et al 2013) also regulated both cell growth and microtubule activity. The interaction genes may thus provide useful clues to the relationship between growth inhibition and paclitaxel action ( Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, FSIP1 regulates growth of triple-negative breast cancer cells and also resistance to docetaxel, a drug in the same class as paclitaxel (Liu, Sun, et al 2018). SIKE1 (Sonnenschein et al 2018) and CPT1A (Li, Zhao, et al 2013) also regulated both cell growth and microtubule activity. The interaction genes may thus provide useful clues to the relationship between growth inhibition and paclitaxel action ( Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…However, we observed that type I IFN genes were reduced such as IRF7, DDX3X, DDX58, TLR13, TLR9, STING, and IFIT1, which was possibly caused by the ncp BVDV viral particles [12,13]. On the other hand, upregulated DEGs, such as NLRX1, CYLD, SIKE1, ATG12, and RNF125, were shown to interfere with host immune responses in previous documents [23][24][25][26].…”
Section: Discussionmentioning
confidence: 71%
“…This study found common groups of genes related to important cellular processes at 2 hpi. For example, inhibition of NF-κB activation was induced by upregulated IKKE and SIKE1, negative regulators of the NF-κB signaling pathway, and by downregulated p65/RelA-NF-κB [26]. These inhibitory actions could lead to blocked or delayed antiviral responses (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibits TLR3-mediated activation of interferonstimulated response elements (ISRE) and the IFN-beta promoter. May act by disrupting the interactions of IKBKE or TBK1 with TICAM1/TRIF, IRF3 and DDX58/RIG-I [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…SIKE1, IKK-epsilon, and TBK1 genes are physiological inhibitors that act on viral and TLR3triggered IRF3 to inhibit TLR3-mediated interferon-stimulated response elements (ISRE) and IFN-β promoters. Activation of the ISRE and IFN-β promoters can be achieved by disrupting the interaction between IKBKE or TBK1 and TICAM1/TRIF, IRF3, and DDX58/RIG-I, which does not inhibit the NF-κB activation pathway [27,28].…”
Section: Discussionmentioning
confidence: 99%